Investigation of Geothermal Using Magnetotelluric Method in Babakan Bogor, Bengkulu Province, Indonesia - Muhammad Farid; Arif Ismul Hadi; Lusi Puspita Sari (Indonesian Journal on Geoscience, 2021)
DOI:10.17014/ijog.8.2.221-231Bengkulu Province, due to be crossed by Bukit Barisan Mountains has relatively large geothermal reserves. This study aims to investigate the geothermal reserves in Babakan Bogor Village, Kepahiang Regency, Bengkulu Province. The magnetotelluric (MT) method with electric and magnetic sensors was used to record data in the fields. The electric sensor consisted of three porous pots, two of which were placed horizontally (Ex, Ey) and the other one vertically (Ez) as the ground. Magnetic sensors with two coils were placed horizontally (Hx, Hy) and one vertically (Hz). The data obtained in the field are in the form of rock resistivity values which are correlated with geothermal potential, so that the reservoir could be determined. Data recording in the fields used low frequencies, i.e. 128 Hz. Data processing was done using MAPROS software to convert time-series data to EDI file types. Input data in the MAPROS software is in the form of apparent resistivity vs. depth values. Furthermore, an inversion was carried out to obtain the true resistivity value as the output of the software. ZONDMT1 and ZONDMT2 were used to model the resistivity values in one dimension (1D) and two dimensions (2D). The results showed that there were geothermal reserves in the Babakan Bogor Village, Kepahiang Regency, at a depth of 1,500 to 5,000 m.